Intraoperative cholangiography during elective laparoscopic cholecystectomy: selective or routine use? - Alex Augusto Silva; Carlos Augusto Canteras Raposo Camara; Aiodair Martins Júnior; Celso Júnior Oliveira Teles; Júverson Alves Terra Júnior; Eduardo Crema (Acta Cirúrgica Brasileira, 2013)
PURPOSE: To investigate clinical, laboratory and ultrasonographic parameters in patients with and without preoperative criteria for intraoperative cholangiography (IOC) during laparoscopic cholecystectomy in order to define predictive factors of choledocolithiasis. METHODS: As a criterion for inclusion in the study the patients should present chronic calculous cholecystitis in the presence or absence of any recent clinical, laboratory of ultrasonographic finding suggesting choledocolithiasis, who were therefore submitted to cholangiography during surgery. RESULTS: A total of 243 laparoscopic cholecystectomies with IOC were performed on patients with chronic calculous cholecystitis with or without a preoperative formal indication for contrast examination. Choledocolithiasis was detected in 33 (13.58%) of the 243 patients studied. The incidence of previously unsuspected choledocolithiasis was only one case (1.0%) among 100 patients without an indication for this exam. However, 32 (22.37%) cases of choledocolithiasis were observed among the 143 patients with a preoperative indication for IOC. CONCLUSION: The use of selective cholangiography is safe for the diagnosis of choledocolithiasis. Only 22.37% of the cholangiography results were positive in cases of suspected choledocolithiasis.